A Solution Without a Problem: Judges' Perspectives on the Impacts of the Introduction of Public Defenders on Israel's Juvenile Courts - Borowski, Allan (The British journal of criminology, 2005)
This article reports that Israel's parliament has passed the Public Defenders Act in 1995 to ensure that adults facing criminal proceedings, particularly for serious offences, have access to legal representation when they could not afford a private attorney. According to the Director of the Public Defenders Office (PDO), professor Kenneth Mann, the extension of coverage to the youngsters appearing before the Juvenile Court was a natural outgrowth of the general orientation of the PDO. Further, even before the PDO became operational, senior officials in the Attorney-General's Department and Ministry of Justice had acknowledged that the absence of legal representation in the Juvenile Court was a problem. In essence, then, public defender representation for juveniles charged with criminal offences was introduced in Israel on the coattails of a much bolder initiative in the adult criminal justice system